The Impact of Business Support Services for Small and Medium Enterprises on Firm Performance in Low -and Middle- Income Countries: A Meta-Analysis - Túlio Cravo; Caio Piza (Inter-American Development Bank (IDB), 2016)
Interventions designed to support small and medium enterprises (SMEs) are popular among policy makers, given the role SMEs play in job creation around the world. Business support interventions in low- and middle-income countries (LMICs) are often based on the assumption that market failures and institutional constraints impede the growth of SME growth. Significant resources from governments and international organizations are directed to SMEs to maximize their socioeconomic impact. Business-support interventions in LMICs most often relate to formalization and business environments, exports, value chains and clusters, training and technical assistance, and access to credit and innovation. Very little is known about the impact of such interventions despite the abundance of resources directed to SME business-support services. This paper systematically reviews and summarizes 40 rigorous evaluations of SME-support services in LMICs and presents evidence to help inform policy debates. The study found indicative evidence that overall business-support interventions help improve firm performances and create jobs. However, little is still known about which interventions work best for SMEs and why. More rigorous impact evaluations are needed to fill the large knowledge gap in the field.
hdl:11319/7745
Keywords: J21; J48; O10; 330; SMEs; Impact Evaluation; Private Sector Development; Firm Performance